Can resilience promote calling among Chinese nurses in intensive care units during the COVID-19 pandemic? The mediating role of thriving at work and moderating role of ethical leadership - Sun, Tao; Zhang, Shu-e; Yin, Hong-yan; Li, Qing-lin; Li, Ye; Li, Li; Gao, Yu-fang; Huang, Xian-hong; Liu, Bei (Frontiers in Psychology, 2022)
Background Nurses working in the intensive care unit (ICU) clung tenaciously to their job during the COVID-19 pandemic in spite of enduring stressed psychological and physical effects as a result of providing nursing care for the infected patients, which indicates that they possessed a high degree of professionalism and career calling. The aim of this study was to explain the associations between resilience, thriving at work, and ethical leadership influencing the calling of ICU nurses. Methods From December 2020 to January 2021 during the COVID-19 pandemic, a cross-sectional survey of 15 provinces in China was conducted using an online questionnaire. A total of 340 ICU nurses (effective response rate: 64.89%) completed sufficient responses to be used in the study. Sociodemographic factors, job demographic factors, resilience, calling, thriving at work, and ethical leadership were assessed using the questionnaire. General linear modeling (GLM), hierarchical linear regression (HLR) analysis, and generalized additive model (GAM) were performed to examine all the considered research hypotheses. Results Resilience was positively and significantly associated with calling. Moreover, thriving at work partially mediated the relationship between resilience and calling. The indirect effect of resilience on calling was 0.204 (p < 0.0001), and the direct effect of resilience on calling through thriving at work was 0.215 (p < 0.0001). The total effect of resilience on calling was 0.419 (p < 0.0001). In addition, ethical leadership played a moderating role in the relationship between resilience and calling (β = 0.16, p < 0.05). Conclusion Greater resilience can positively predict increased calling among Chinese ICU nurses during the COVID-19 pandemic. Moreover, thriving at work is a mechanism that partly transmits the positive effects of resilience on calling. Overall, nurses possessing greater resilience tend to maintain thriving at work in the face of such adversity, further resulting in subsequently increased calling. Besides, findings suggest that there is stronger influence of resilience on calling among nurses working in an organization managed by an ethical leader. The current findings may offer two insights for nursing practitioners and policymakers in the postpandemic world. First, resilience training and intervention are necessary to foster nurses' sense of thriving at work in the nursing industry, further promoting career calling. Second, better training and effort on the development of ethical leadership for leaders in nursing practice are essential to encourage followers to engage in social learning of ethical behaviors and abiding by normatively appropriate conduct, further enacting prosocial values and expressing moral emotions.